Ministerial decree No. 22/2014 Amending Some Provisions of the Executive Regulation of the Capital Market Law Issued as per of the Minister of Economy and Foreign Trade No.135 of the year 1993 = قرار وزاري رقم 22 لسنة 2014 بتعديل بعض أحكام اللائحة التنفيذية لقانون سوق رأس المال الصادرة بقرار وزير الاقتصاد والتجارة الخاريجة رقم 135 لسنة 1993 - Egypt. Minister Prime. (2025)
Ministry of investment decree No. 22 of the year 2014 Amending some Provisions of the Executive Regulation of the Capital Market Law Issued as per decree of the minister of economy and foreign trade no. 135 of the year 1993 وزارة الاستثمار قرار رقم 22 لسنة 2014 بتعديل بعض أحكام اللائحة التنفيذية لقانون سوق رأس المال الصادرة بقرار وزير الاقتصاد والتجارة الخارجية رقم 135 لسنة 1993